La gestion des ressources humaines dans les usines de munitions durant la Deuxième Guerre mondiale: le cas de la General Engineering Company - Labbé, Pierrick (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2010)
Abstract This article examines human resources management in the General Engineering Company plant at Scarborough during World War II. A study of this case, conceptualized to include the structural characteristics of the capitalist economy and government intervention, demonstrates how the private sector and the labour market were key factors in transforming working conditions during this period. The importance of the production of certain military items for the war eﬀort resulted in a collaboration between the government and private companies to ensure a stable workforce. The strategies used to assure continuity of production, such as the choice of a female workforce, the adoption of measures of welfare capitalism or the struggle against outside unions, contributed to the transformation of the workplace and the development of the work environment unique to the period of the war and to factories financed by the federal government.